Predictors of survival after hepatic resection among patients with colorectal liver metastasis - Wang, X (Nature Publishing Group, 2007)
Studies suggest improved survival following resection of colorectal cancer liver metastases (CLMs). We investigated predictors of survival among patients with CLM who underwent hepatic resection using the SEER-Medicare database to identify patients ⩾65 years diagnosed with CLM, 1991–2003, who underwent hepatectomy. Cox proportional hazards models were used to identify factors associated with survival after hepatectomy. Of 923 patients with CLM who underwent hepatectomy, 514 were stages I–III and developed CLM>6 months after diagnosis (metachronous), and 409 were stage IV with CLM at diagnosis (synchronous). From the date of hepatectomy, 5 year survival was 22%; younger age, being married, female gender, surgery in an NCI-designated cancer centre, fewer comorbidities, fewer positive lymph nodes, and lower grade were associated with improved survival. Both 5-fluorouracil (5FU)-based chemotherapy and hepatic arterial infusion (HAI) of floxuridine-based chemotherapy following hepatectomy improved survival (HR=0.62, 95% CI: 0.50–0.78; HR=0.51, 95% CI: 0.28–0.97, respectively) in the synchronous, but not metachronous, group. The HR for overall mortality was higher in hospitals with a high vs low procedure volume (0.75, 95% CI: 0.58–0.94). A substantial subgroup of patients with CLM who undergo hepatectomy experiences long-term survival. High hospital procedure volume and use of 5FU-based or HAI-based chemotherapy after resection were associated with improved prognosis.